TELOGOREJO HOSPITAL BED PREDICTION 2021-2022 - Nias Amelia Rahmawati; Evina Widianawati; Suyoko Suyoko; Widya Ratna Wulan (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
AbstractBackground. Hospital statistical indicators during the Covid-19 pandemic will be different from normal conditions before covid-19, One of the indicators for inpatient services is BOR which is the percentage of bed usage with Barber Johnson's ideal standard of 75-85%. During a pandemic, BOR information is needed to assist hospitals in terms of speed of service and policies in the use of beds and rooms. The purpose of this research is to predict the bed at Tlogorejo Hospital in 2021-2022. Method. This type of research is quantitative descriptive and uses secondary data, the data used is from March 2020 - June 2021 by way of observation. Result. The study results from the Barber Johnson chart with linear bed predictions are not efficient from July 2021 - May 2022 and efficient from July 2021 - May 2022. June 2021 - Dec 2022 while the results of the barber johnson chart predict beds with a BOR of 75% that all wards from July 2021-Dec 2022 are efficient. Conclusion. Therefore it is recommended to Tlogorejo hospital to add beds according to the predicted results of beds BOR 75 % or predicted results of bed Linier.Keywords: Predictions, beds, barber johnson charts and BOR.